Propuesta de un sistema de gestión ambiental basado en la norma ISO 14001:2015 para la Avícola Mía, cantón Bolívar - Montesdeoca Zambrano, Génesis Penélope (2025)
This research was carried out at Avícola Mía, located in the city of Calceta, Bolívar canton, whose objective was to propose an Environmental Management System based on the ISO 14001:2015 standard for the mitigation of its negative impacts. Methods were used that facilitated the collection of information in the study area, along with techniques that contributed to obtaining relevant data. As part of the procedure, the current situation of the company was diagnosed, through a field trip and an interview with its owner. The environmental aspects and impacts related to the poultry operations were identified and assessed, through qualitative and quantitative matrices (Hernández, 2021) that facilitated this process. The design of an EMS was carried out, in accordance with the requirements of the aforementioned standard. The results of the diagnosis show that the company develops practices such as the production of fertilizer from excreta and the reuse of water in irrigation tasks; However, shortcomings were also detected in several environmental aspects that were confirmed in the next investigative stage. Through the identification and assessment matrix of environmental impacts, aspects such as energy consumption, generation of odors, proliferation of insects, generation of hazardous waste and GHG emissions were found, which negatively impact the environment. Based on these results, an EMS was proposed with the purpose of providing the company with the necessary guidelines to align its daily activities with sustainable practices.